Serum Levels and Placental Expression of NGAL in Gestational Diabetes Mellitus - Xiaoqian Yin; Yan Huo; Li Liu; Yixing Pan; Suxin Liu; Runfang Wang (International Journal of Endocrinology)
Objectives. The aim was to investigate neutrophil gelatinase-associated lipocalin (NGAL) levels in the serum and term placentas and its potential role in gestational diabetes mellitus (GDM). Methods. A total of 49 GDM subjects and 39 age-matched women with normal pregnancies were recruited. We examined serum concentrations of NGAL and tumor necrosis factor-α (TNF-α) in maternal blood and cord blood and their expression levels in the term placentas and umbilical cord. Results. Serum NGAL levels were significantly higher in GDM patients than in normal pregnant controls both in the maternal blood (4.80 ± 1.99 vs. 3.66 ± 1.13, P=0.001) and the cord blood (4.70 ± 2.08 vs. 3.85 ± 1.44, P=0.027). Moreover, serum NGAL levels exhibited a positive correlation with various parameters of insulin resistance. Maternal serum NGAL levels positively correlated with the NGAL levels found in the cord blood of the control (r = 0.399, P=0.012) and the GDM subjects (r = 0.349, P=0.014). Finally, the expression of NGAL protein levels in the placenta (1.22 ± 0.39 vs. 0.65 ± 0.23, P<0.001) and umbilical cord (0.65 ± 0.23 vs. 0.25 ± 0.10, P<0.001) were higher in GDM women than those noted in the control subjects. In the GDM group, maternal serum NGAL levels exhibited a positive correlation with placental NGAL mRNA and protein levels (r = 0.848, P=0.008; r = 0.636, P=0.011, respectively). Conclusions. NGAL may be an important adipokine involved in GDM and fetal development. The oversecretion of NGAL from the placenta may contribute to the elevated levels of serum NGAL in gestational diabetes mellitus.